(untitled) (Praxis Educativa, 2023)
In this paper we address the methodology and some results of an applied research project aimed at revalorization of Maya language (maayat’aan); most of the participants are students, whose families have interrupted the Maya language transmission. We draw on the premises of a reflexive workshop and the methodology of personal networks, which enable the family memory reconstruction, autobiographical work, and the creation of intersubjective bonds between peers. We present the cases of three participants that allow to observe three particular processes, through which the language revalorization occurs on the subjective level. On the intersubjective level, sharing stories, feelings, and ideas allows to transit “from solitary individual existence to community social existence” (Kaplún, 1988, p. 60). This is manifested in the creation, by the project participants, of a juvenile group that fosters the Maya language.